Inflation - why did it rise and what are the drivers ahead? - Thomas Harr; Morten Spange (Danmarks Nationalbank, 2023)
Since early 2021, consumer price inflation has risen sharply across the advanced economies, including the US, the euro area and Denmark. We argue that the surge in inflation in the three economies in 2021-22 reflects multiple factors, including the Covid19 pandemic in 2020-21 and the Russian war in Ukraine in 2022, as well as the associated policy responses. In 2023-24, at least three factors are likely to drive inflation across the three economies: (a) more stable energy prices, (b) an expected slowdown in aggregate demand growth caused in part by tighter monetary policy, and (c) improving supply chains. Wellanchored inflation expectations mitigate the risk of a price-wage spiral, but backward-looking wage expectations and expansive fiscal policy in the euro area pose risks. While there are a number of similarities with 1970s, there are also important differences. Importantly, central banks are more independent of political influence and they are endowed with explicit mandates for price stability. Moreover, wage indexation has become much less widespread.
Keywords: 330; Inflation; Verbraucherpreisindex; Wirtschaftslage; Dänemark; Eurozone; USA